The Earliest Stage of Lung Adenocarcinoma: the Pathological Diagnosis and Clinical Significance of Adenocarcinoma In Situ - Huikang XIE (Chinese Anti-Cancer Association; Chinese Antituberculosis Association, 2021)
The International Agency for Research on Cancer (IARC) published the World Health Organization (WHO) classification of thoracic tumors (5th edition) in May 2021, only six years after the 4th edition of WHO Classification. With the application of low-dose spiral computed tomography (CT) as an early screening method for lung tumors in recent years, lung adenocarcinoma has become the main type of disease in many hospital surgical treatments. The WHO classification serves as the authoritative guide for pathological diagnosis, and any slight change in the classification is at the heart of pathologists, clinicians and patients. Adenocarcinoma in situ is a newly added type of adenocarcinoma diagnosis in the 4th edition of the WHO classification, and it is also the focus of clinical treatment and research at home and abroad in recent years. Because its catalog position has been adjusted in the 5th edition of the WHO classification, there has been a huge controversy and discussion among clinicians and patients that "adenocarcinoma in situ was excluded from the category of malignant tumors". This article will briefly explain the origin of the diagnosis of lung adenocarcinoma in situ, the adjustment of the new classification catalog, and whether adenocarcinoma in situ is benign or malignant.